9 SURGICAL TECHNIQUES AND POTENTIAL OF MEDIASTINAL LYMPHADENECTOMY IN ROBOTIC SURGERY. (17th September 2021) - Oshikiri, Taro; Takiguchi, Gosuke; Urakawa, Naoki; Hasegawa, Hiroshi; Yamamoto, Masashi; Kanaji, Shingo; Matsuda, Yoshiko; Yamashita, Kimihiro; Matsuda, Takeru; Nakamura, Tetsu; Suzuki, Satoshi; Kakeji, Yoshihiro
Abstract: : Procedure of minimally invasive esophagectomy in prone position (Conventional prone-MIE) is standardized leading to feasible short outcomes. On the other hand, robot assisted MIE (Robotic MIE) was approved as Japanese health insurance treatment since 2018. Especially, reduction of recurrent laryngeal nerve (RLN) palsy leading to aspiration pneumonia is expected for Robotic MIE. The purpose of this study is to clarify the potential of Robotic MIE for improvement of short outcomes. Methods: Twenty-four Robotic MIEs in introduction period since 2018 and 128 Conventional prone-MIEs in established period since 2015 from all of the 375 cases were compared using propensity score matching. Results: Operative times in both entire and thoracic procedures were significantly longer in Robotic MIE. There were no significant differences between two groups in the number of harvested lymph nodes, amount of the blood loss, left RLN palsy rate (13% vs 14%, > Clavien-Dindo classification: C-D grade I), right RLN palsy rate (4% vs 8%, > C-D grade I), and pneumonia rate (7% vs 7%, > C-D grade II). Conclusion: Short outcomes of Robotic MIE in introduction period were not inferior to those of Conventional prone-MIE in established period. More improvement is expected for Robotic MIE via learning curve. In conclusion, Robotic MIE has hidden potential to outstrip Conventional prone-MIE in outcomes. Video: https://www.dropbox.com/s/7byc8nsqupgetsp/2020%20ISDE%20movie%20for%20submission.wmv?dl=0 .